Immaterial Inheritance: The Socialization of Cultures of Housing Consumption. Issue 3 (3rd July 2019) - Nethercote, Megan
Abstract: This article progresses understandings of contemporary middle-class housing aspirations and the socialization of these within families. It examines Australian middle-class homeowners' dispositions towards mortgage debt, using qualitative Bourdieusian analytics. By avoiding the common reduction of housing aspirations to tenure preferences, it foregrounds diverse orientations towards home-buying that suggest cultural forms of middle-class heterogeneity in the housing field. It then identifies how within-family socialization conditions these differing orientations, including through parental guidance and observational learning. This "immaterial inheritance" variously promotes and deters property speculation, for instance by imparting competence (e.g. housing literacy) and confidence to invest, and thus begins to shed light on the under-explored cultural dimensions of class in intensifying housing commodification. Sharper understandings of the trajectories of cultural capitals over time (and their interaction with trajectories of economic capitals), hold promise for explaining how these calibrate the way intergenerational transfers shape inequality.